2012
DOI: 10.3382/ps.2012-02333
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of probiotic strains for development of fermented Alisma canaliculatum and their effects on broiler chickens

Abstract: The present study was conducted to select appropriate microbial strains for the development of fermented Alisma canaliculatum A. Br. et Bouche (FAC) feed additive and to examine their effects on broilers. In experiment 1, 16 strains of Lactobacillus acidophilus, Lactobacillus plantarum, Enterococcus faecium, Bacillus subtilis, Bacillus coagulans, and Saccharomyces cerevisiae from the Korean Collection for Type Cultures (KCTC) were evaluated. The strains were tested for their acid, bile, and heat tolerance leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 49 publications
2
22
1
Order By: Relevance
“…Rahman & Kim (2016) reported that dietary supplementation of Nigella sativa seed (source of antioxidant) increased the protein content of broiler meat, whereas Marzoni et al (2014) showed no effect of dietary natural antioxidants (dry extracts of tomato skin, orange peel, and green tea leaves) on the crude protein content of breast and thigh meat of broiler chickens and Muscovy ducks. With regard to the effect of AGPs on crude protein content of meat, the present findings were different from those reported by other workers, which showed no effect of various AGPs, for example 0.05% chlortetracycline and HCL + cyanocobalamin (Yang et al, 2003), 0.5 g/kg flavomycin (Attia et al, 2011), 0.005% oxytetracycline (Hossain et al, 2012), and 100 ppm combination of oxytetracycline and neomycin (Abdulla et al, 2017). The rationale for this condition is not fully known, but the various types and doses of AGPs and the conditions of the study may partly explain the conflicting results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Rahman & Kim (2016) reported that dietary supplementation of Nigella sativa seed (source of antioxidant) increased the protein content of broiler meat, whereas Marzoni et al (2014) showed no effect of dietary natural antioxidants (dry extracts of tomato skin, orange peel, and green tea leaves) on the crude protein content of breast and thigh meat of broiler chickens and Muscovy ducks. With regard to the effect of AGPs on crude protein content of meat, the present findings were different from those reported by other workers, which showed no effect of various AGPs, for example 0.05% chlortetracycline and HCL + cyanocobalamin (Yang et al, 2003), 0.5 g/kg flavomycin (Attia et al, 2011), 0.005% oxytetracycline (Hossain et al, 2012), and 100 ppm combination of oxytetracycline and neomycin (Abdulla et al, 2017). The rationale for this condition is not fully known, but the various types and doses of AGPs and the conditions of the study may partly explain the conflicting results.…”
Section: Discussioncontrasting
confidence: 99%
“…Concomitant results were reported by Hossain et al (2012) and Nie et al (2015), in which dietary supplementation with fermented Alisma canaliculatum and Candida tropicalis-fermented cotton seed, respectively, increased the crude protein content of breast meat of broiler chicks. The mechanism by which AC-FCP increased the protein content of breast meat is unclear, but the enhancing effect of probiotic fungus grown in AC-FCP on the protein efficiency ratio and thus production of protein in the musculature of broilers may be the reason (Khaksefidi & Rahimi, 2005;Hossain et al, 2012). In terms of the effect of antioxidants on the crude protein content of breast meat, the data in the literature are inconclusive.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, in our study, there were sporadic changes in heart and liver weights affected by the dietary treatments. Similar changes in digestive organ weights were previously reported with the diet fermented with yeast inoculant at 10 6 cfu kg −1 (Chen et al, 2013, Hossain et al, 2012Chen et al, 2009). In our study, the changes in digestive organ weights were similarly reflected on the changes in the lengths of entire digestive tract, foregut, and small intestine ( Table 5).…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, this study investigated the beneficial effects of a combined two-stage fermented CJ inoculated with multispecies probiotics bacteria such as Bacillus subtilis, Lactobacillus acidophilus, Enterococcus faecium and S. cerevisiae on the growth performance, humoral immunity, caecal microbiology and meat oxidative stability in broilers. Hossain et al (2012b).…”
Section: Introductionmentioning
confidence: 95%